176. Evaluation of automated VMAT planning for complex pelvic treatments. (December 2018) - Ianiro, A.; Deodato, F.; Macchia, G.; Buwenge, M.; Valentini, V.; Morganti, A.G.; Cilla, S.
Abstract: Purpose: Treatment plans for high-risk prostate an gynecological cancer are highly complex due to large irregular-shaped pelvic target volumes, to multiple dose prescription and to several organs at risk (OARs) close to the target. The quality of these plans is highly inter-planner dependent. We assessed the performance of the Auto-Planning module present in the Pinnacle 3 TPS (version 16.0), comparing automatically generated VMAT plans (AP) with the historically clinically accepted manually-generated ones (MP). Methods: Twenty-four consecutive patients treated with VMAT-SIB for high-risk prostate and endometrial cancer were re-planned with the Auto-Planning engine. For each patient, the AP plan was compared with two MP plans (using Oncentra Masterplan and Pinnacle TPS, respectively) The PTV1 included the primary tumor (prostate or vaginal vault); the PTV2 included the pelvic lymph-nodes. The two target volumes were simultaneously irradiated over 25 daily fractions at 65 Gy/55 Gy and 45 Gy to the PTV1 and PTV2, respectively. All plans were created by means of the "dual arc" feature. For AP plans, a progressive optimization algorithm is used to continually adjust initial targets/OARs objectives. Various dose and dose-volume metrics for target volumes and OARs, as well as conformity (CI) indexes and healthy-tissue integral dose (ID) were evaluated. Results: Differences in all dose coverage metrics (V95%, D98%, D50%, D2% and Dmean) for both PTVs were not statistically significant (p < 0.05). Also for rectum, bladder and small bowel, differences in DVHs were no significant in overall dose range. AP plans provided a significant decrease in Integral Dose of 5.1% and an increased conformity for PTV2 (MP:1.59 vs. AP:1.46). The mean number of MUs was slighter greater for AP plans. The average effective working time was significantly reduced. Conclusions: The Pinnacle 3 Auto-Planning module achieved highly consistent treatment plans also in the cases of complex anatomical sites.